On perform arithmetic operations in negative binary system - Тарасенко, В. П.; Король, І. Ю. (Problems of Informatization and Control, 2008)
The question of performing arithmetic operations in negative binary system , and some clarification of known algorithms and obtained new algorithms conversion from decimal and binary number systems in binary minus and vice versa. Obtained a series of algorithms perform arithmetic operations that will be the basis of specialized computer software and computer systems